Knowledge foundation in green purchase behaviour: Multidimensional scaling method - Mohammad Hossein Marvi; Morteza Maleki Minbashrazgah; Azim Zarei; Golnar Shojaei Baghini (Cogent Business & Management, 2020)
For the past few decades, because of the environmental hazards, green purchase has been subject to wide ranges of studies. Subsequently, understanding the intellectual structure of the green purchase behaviour is increasingly becoming important. This study investigates the citation in green purchase academic literature and it analyses the knowledge structure in it. The following bibliometric analysis comprised 86 green purchase articles. By employing multidimensional scaling (MDS) to identify the ranges of the intellectual influences and shaped green purchase behaviour. The knowledge structure in green purchase is discovered by employing co-citation analysis to find the most important and effective studies in the green purchase study domain. A conceptual framework is developed and finally the future model was proposed.
Keywords: 650; research method; green purchase; multidimensional scaling; bibliometric studies; theory of planned behaviour